2007
DOI: 10.1063/1.2743731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Li-codoping on the radiation hardness of CsBr:Eu2+

Abstract: The poor radiation hardness of the otherwise excellent x-ray storage phosphor CsBr:Eu2+ constitutes a problem for its commercial application in medical diagnostics. X-ray induced vacancy centers such as M-centers enhance the diffusion of Eu2+ activators resulting in a formation of photostimulated luminescence (PSL) inactive europium clusters or second phases of europium compounds. The present study investigates the influence of Li-codoping on the radiation hardness of CsBr:Eu2+. It is reported that the integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Improvement of the radiation hardness is expected. A recent work, 30 for example, investigated the influence of lithium ͑Li͒ codoping on the radiation hardness of CsBr: Eu 2+ . It was reported that the integration of Li + into the CsBr: Eu 2+ lattice suppressed the generation of M centers during x ray irradiation and thereby partially improved the radiation resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of the radiation hardness is expected. A recent work, 30 for example, investigated the influence of lithium ͑Li͒ codoping on the radiation hardness of CsBr: Eu 2+ . It was reported that the integration of Li + into the CsBr: Eu 2+ lattice suppressed the generation of M centers during x ray irradiation and thereby partially improved the radiation resistance.…”
Section: Discussionmentioning
confidence: 99%
“…20 While co-doping this material with lithium (Li) has been explored as a way to slow the agglomeration of activator ions, the sensitivity loss remains significant (50% after 25 Gy) by radiation therapy standards. 21,22 The present work offers the first systematic investigation into the radiation hardness of KCl:Eu 2þ . The prototype dosimeters used in this study were manufactured by using the solid state reaction methods.…”
Section: Introductionmentioning
confidence: 98%
“…15 Jursinic suggested that Al 2 O 3 :C dosimeters could be used for accurate radiation therapy dosimetry if the sensitivity and extent of supralinearity were established for each dosimeter in use. 15 Recent research [16][17][18][19] into an emerging diagnostic CR material, CsBr:Eu 2þ , however, has found a rapid loss of signal with cumulated dose, [20][21][22] prob-ably resulting from radiation-mediated agglomeration of activator ions (Eu 2þ ) in this material, which leads to luminescence quenching. 23 It has been reported that CsBr:Eu 2þ maintains only 10% of its initial sensitivity after 100 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…However, in order for an electron to tunnel to a nearby V k center, the F center must be physically close (spatially correlated) to the V k center. Thus, PSL yield at low temperatures corresponds to the concentration of spatially correlated traps [10, 11]. …”
Section: Resultsmentioning
confidence: 99%